On Modular Inequalities for Generalized Hardy Operators on Weighted Orlicz Spaces - Almohammad, Khaleel (Eurasian Mathematical Journal, 2021)
The purpose of this paper is to study the behaviour of Hardy-type operator on weighted Orlicz spaces. The results on modular inequalities for the considered operators of Hardy type are important, since such operators arise in the study of decreasing rearrangements for generalized Bessel and Riesz potentials, in which case Orlicz–Lorentz space serves as an underlying space.